2019
DOI: 10.7752/jpes.2019.02174
|View full text |Cite
|
Sign up to set email alerts
|

Untitled

Abstract: The purpose of this study was to quantify the competitive balance in both men's and women's professional division roller hockey competitions (Spanish and Portugal leagues) comparing the results obtained according to the sex of participants. The sample was composed of 5,942 roller hockey games (2,044 in Spanish male league, 1,580 in Spanish female league, 1,814 in Portuguese male league and 504 in Portuguese female league) between the 2009-2010 and 2017-18 seasons. To calculate the competitive balance, it was u… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 16 publications
0
3
0
Order By: Relevance
“…Based on the present results, it can be observed that this influence of teams' level on match outcomes has a higher effect on female than in male rink hockey [20]. The reason can be attributed to the presence of a higher level of bias in female competitions in comparison to male competitions, likely stemming from the higher varying budgets of female teams competing in the same division [32]. This budget disparity leads to higher-level heterogeneity compared to rink hockey male leagues, where both professional and amateur athletes participate in the same competitions.…”
Section: Team Level and Opponent's Levelmentioning
confidence: 46%
“…Based on the present results, it can be observed that this influence of teams' level on match outcomes has a higher effect on female than in male rink hockey [20]. The reason can be attributed to the presence of a higher level of bias in female competitions in comparison to male competitions, likely stemming from the higher varying budgets of female teams competing in the same division [32]. This budget disparity leads to higher-level heterogeneity compared to rink hockey male leagues, where both professional and amateur athletes participate in the same competitions.…”
Section: Team Level and Opponent's Levelmentioning
confidence: 46%
“…This particular case scenario is very common in rink hockey, where there is evident bias caused by the different budgets of teams competing in the same division [ 44 ]. This issue causes more level heterogeneity than in other team sports with professional and semi-professional athletes in the same competitions [ 45 ]. For this reason, among the different situational variables, the level of teams has been reported as one of the most decisive variables in rink hockey match outcomes [ 46 ].…”
Section: Discussionmentioning
confidence: 99%
“…This lack of significance could be attributed to the same reasons that explain the lack of interaction of match level. In rink hockey competitions with a level bias [ 30 , 31 ], the same teams competed for the championship across the different seasons.…”
Section: Discussionmentioning
confidence: 99%